Gaya Kepemimpinan Untuk Kinerja Karyawan Pada Koperasi Unit Desa Karya Mukti Kecamatan Pelepat Ilir - Zuhenda, Reza; Darmawanto, Darmawanto; M, Ariyanto; Syahwami, Syahwami; Rusnaini, Sasmita; Hamirul, Hamirul (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
This study aims to determine how much influence leadership style has on employee performance at KUD Karya Mukti. The data obtained in this study were collected through the distribution of questionnaires to 43 respondents and the sampling technique used was total sampling technique. The power analysis used is multiple linear regression and the results of the questionnaire are processed using the SPSS Version 16 program. Based on the results of the assessment that has been carried out, it can be seen that the directive leadership style (XI), supportive leadership style (X2), participatory leadership style (X3), and achievement-oriented leadership style (X4) have an influence on employee performance (Y). This can be proven from the value of R Square which is 0.691% while the remaining 31.9% is influenced by other variables.